Types of diversity and ecological functions of pteridophytes in the Lawe Secepit Waterfall Kendal - Ulfah, Maria; Santoso, Luhur Pujo; Alamsyah, Ricky; Setyaningrum, Sulis; Kurniawati, Septiana (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.